2022
DOI: 10.3390/ijms231911505
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Defensin Antimicrobial Peptides and Their Expression in Bed Bugs in Response to Bacterial Ingestion and Injection

Abstract: Common bed bugs, Cimex lectularius, can carry, but do not transmit, pathogens to the vertebrate hosts on which they feed. Some components of the innate immune system of bed bugs, such as antimicrobial peptides (AMPs), eliminate the pathogens. Here, we determined the molecular characteristics, structural properties, and phylogenetic relatedness of two new defensins (CL-defensin1 (XP_024085718.1), CL-defensin2 (XP_014240919.1)), and two new defensin isoforms (CL-defensin3a (XP_014240918.1), CL-defensin3b (XP_024… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 91 publications
2
4
0
Order By: Relevance
“…In prior work, RT-qPCR revealed significant upregulation of CL-defensins and CL-prolixicins in response to ingestion of bacteria ( 69 ), supporting the results of this study. In summary, three defensin genes (CL- defensins 1, 2, and 3) were among the most up-regulated genes in pair-wise comparisons between midgut/controls and either midgut/Gr+ or midgut/Gr– samples (see 3.2; Figures 3 , 4 ; Supplementary Table S4 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In prior work, RT-qPCR revealed significant upregulation of CL-defensins and CL-prolixicins in response to ingestion of bacteria ( 69 ), supporting the results of this study. In summary, three defensin genes (CL- defensins 1, 2, and 3) were among the most up-regulated genes in pair-wise comparisons between midgut/controls and either midgut/Gr+ or midgut/Gr– samples (see 3.2; Figures 3 , 4 ; Supplementary Table S4 ).…”
Section: Resultssupporting
confidence: 90%
“…Among these, defense- and immunity-associated genes were prominently up-regulated. Key genes include CL-defensin3 (LOC106661791), CL-defensin2 (LOC106661792), and CL-defensin1 (LOC106661793), which are modulated by the Imd and Toll pathways ( 68 , 69 ). The lysozyme-like gene (LOC106663700) aligns with the c-type lysozymes RpLys-A (EU250274) and RpLys-B (EU250275) from Rhodnius prolixus ( 70 ) that function in both digestion and immune defense by targeting bacterial cell walls ( 70 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annotations of the bed bug genome showed that, similar to other hemipteran insects, their immune repertoire is lacking in some canonical insect immune-related genes such as parts of the Imd pathway [14,23]. Along with this, bed bugs have a relatively low number of identifiable AMPs, with genes encoding three defensin AMPs and two diptericin-like putative AMPs [14,24]. Previous studies found that the three defensin AMPs are upregulated in response to various bacterial challenges, and another study found the two diptericin-like genes expressed in bed bug hemocytes [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…Along with this, bed bugs have a relatively low number of identifiable AMPs, with genes encoding three defensin AMPs and two diptericin-like putative AMPs [14,24]. Previous studies found that the three defensin AMPs are upregulated in response to various bacterial challenges, and another study found the two diptericin-like genes expressed in bed bug hemocytes [17,24]. Along with this, several studies have shown that bed bug extracts have antimicrobial properties [2527].…”
Section: Introductionmentioning
confidence: 99%